2006
DOI: 10.3310/hta10380
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the cost-effectiveness of five strategies for the prevention of non-steroidal anti-inflammatory drug-induced gastrointestinal toxicity: a systematic review with economic modelling

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(65 citation statements)
references
References 162 publications
3
57
0
4
Order By: Relevance
“…217 Further, in the year before the withdrawal, the authors of a systematic review had written directly to the primary author of every published trial of rofecoxib asking about cardiovascular events and major bleeds; however, they received only a single reply and it did not provide data on cardiovascular events. 218 In a more recent case study, Psaty and Kronmal (2008) found biased reporting of findings from clinical trials of rofecoxib for Alzheimer's disease or cognitive impairment. 219 Before its withdrawal, rofecoxib had been used in more than 80 million patients.…”
mentioning
confidence: 99%
“…217 Further, in the year before the withdrawal, the authors of a systematic review had written directly to the primary author of every published trial of rofecoxib asking about cardiovascular events and major bleeds; however, they received only a single reply and it did not provide data on cardiovascular events. 218 In a more recent case study, Psaty and Kronmal (2008) found biased reporting of findings from clinical trials of rofecoxib for Alzheimer's disease or cognitive impairment. 219 Before its withdrawal, rofecoxib had been used in more than 80 million patients.…”
mentioning
confidence: 99%
“…Recurrent symptomatic or bleeding ulcers (20% versus 0%) and gastrointestinal bleeding (7.7% versus 0%) were more common in patients on famotidine than in those on pantoprazole (Ng et al, 2010). However, economic modeling suggests that co-therapy with H2 receptor antagonists may be a cost-effective strategy for the prevention of ulcer bleeding in NSAID users (Brown et al, 2006). Like PPIs, there have not been any randomized, clinical outcome trials that evaluate the efficacy of H2 receptor antagonists in chronic NSAID users.…”
Section: H2 Receptor Antagonistsmentioning
confidence: 92%
“…These complications may occur within the first week of treatment [12]. In a recent meta-analysis it was reported that adding a proton pump inhibitor (but not a histamine-2 receptor antagonist) to treatment with NSAIDs will reduce the risk of symptomatic ulcers associated with NSAIDs treatment [13].…”
Section: Discussionmentioning
confidence: 99%